1995
DOI: 10.1042/bj3090721
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid directly stimulates osteoclastic bone resorption and gene expression of cathepsin K/OC-2

Abstract: Vitamin A metabolites such as all-trans-retinoic acid (all-trans-RA) affect several steps of metabolic processes in vertebrates. In the last few years, several studies have shown the effect of RA on bone formation and metabolism. However, mechanisms of its action still remain unclear, especially with respect to the regulation of bone cells. Therefore, this study was carried out to clarify how RA regulates the activity of osteoclasts. Using a pit assay involving unfractionated bone cells, including osteoclasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Using these highly enriched mature osteoclasts, we clarified that estrogen directly inhibited bone resorption and cathepsin K gene expression and induced osteoclastic apoptosis through estrogen receptor ␣ (12, 13). Moreover, we demonstrated that retinoids activated both osteoclastic bone resorption and gene expression of cathepsin K, and of retinoic acid receptor ␣ and retinoid X receptor ␤ were expressed in mature osteoclasts (14).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Using these highly enriched mature osteoclasts, we clarified that estrogen directly inhibited bone resorption and cathepsin K gene expression and induced osteoclastic apoptosis through estrogen receptor ␣ (12, 13). Moreover, we demonstrated that retinoids activated both osteoclastic bone resorption and gene expression of cathepsin K, and of retinoic acid receptor ␣ and retinoid X receptor ␤ were expressed in mature osteoclasts (14).…”
mentioning
confidence: 85%
“…The total RNA was extracted from the cultured cells by the acid guanidinium-phenol-chloroform method. Total RNA was fractionated on a formaldehyde agarose gel by electrophoresis and then blotted onto a nylon membrane for Northern blot analysis (14). 32 PLabeled cDNA probes were prepared by the random primer labeling procedure.…”
Section: Isolation Of Mature Osteoclasts From Rabbit Longmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cathepsin K is highly expressed in ovaries and osteoclasts (57). Retinoic acid is reported to induce transcription and protein accumulation in osteoclastic cell lines (58). Moreover, cathepsin K appears to be upregulated at sites of inflammation.…”
Section: Cathepsin Kmentioning
confidence: 99%
“…In the initial phase of osteoclastic bone resorption, hydroxyapatite crystals are decalcified by acidification of the subosteoclastic microenvironment created by vacuolar-type H ϩ -ATPase, which is highly localized in the ruffled border membranes of osteoclasts (Baron et al, 1985;Vaes, 1988;Sundquist et al, 1990;Vaananen et al, 1990;Sasaki et al, 1994;Yokoya et al, 1997). Resorption lacunae are then formed by degradation of bone type-I collagen, mediated mainly by cathepsin K, a lysosomal cysteine proteinase, which is highly and selectively expressed in osteoclasts (Tezuka et al, 1994;Bromme and Okamoto, 1995;Inaoka et al, 1995;Li et al, 1995;Saneshige et al, 1995;Bossard et al, 1996;Bromme et al, 1996;Drake et al, 1996;Inui et al, 1997;LittlewoodEvans et al, 1997;Kamiya et al, 1998;Yazawa et al, 1998). In concert with cysteine proteinase, acid-soluble and -insoluble type I collagens are thought to be further degraded in the subosteoclastic microenvironment by matrix metalloproteinase-9 (MMP-9, 92-kDa gelatinase/type IV collagenase ϭ gelatinase B) produced by osteoclasts (Everts et al, 1992;Reponen et al, 1994;Wucherpfennig et al, 1994;Okada et al, 1995).…”
mentioning
confidence: 99%